Clinical significance of lipid pathway-targeted therapy in breast cancer - Li, Dan; Jin, Pengcheng; Cai, Yiqi; Wu, Shijie; Guo, Xianan; Zhang, Zhiyun; Liu, Kexin; Li, Panni; Hu, Yue; Zhou, Yunxiang (Frontiers in Pharmacology, 2025)
Globally, breast cancer represents the most common cancer and the primary cause of death by cancer in women. Lipids are crucial in human physiology, serving as vital energy reserves, structural elements of biological membranes, and essential signaling molecules. The metabolic reprogramming of lipid pathways has emerged as a critical factor in breast cancer progression, drug resistance, and patient prognosis. In this study, we delve into the clinical implications of lipid pathway-targeted therapy in breast cancer. We highlight key enzymes and potential therapeutic targets involved in lipid metabolism reprogramming, and their associations with cancer progression and treatment outcomes. Furthermore, we detail the clinical trials exploring the anticancer and cancer chemopreventive activity of therapies targeting these molecules. However, the clinical efficacy of these therapies remains controversial, highlighting the urgent need for predictive biomarkers to identify patient subpopulations likely to benefit from such treatment. We propose the Selective Lipid Metabolism Therapy Benefit Hypothesis, emphasizing the importance of personalized medicine in optimizing lipid pathway-targeted therapy for breast cancer patients.